Advancements in consolidative thoracic radiotherapy following first-line immunotherapy in conjunction with chemotherapy for extensive-stage small cell lung cancer - Liu, Jiang; Liu, Jianhua; Chen, Dadong; Zhu, Yan; Wu, Xiang; Cai, Yin (Frontiers in Immunology, 2025)
Small cell lung cancer (SCLC) presents challenges due to its high invasiveness and rapid progression, resulting in an inferior prognosis. Approximately 70% of patients have developed an extensive stage at the time of diagnosis. While most patients with extensive-stage SCLC (ES-SCLC) are sensitive to chemotherapy, they remain at high risk of local recurrence and distant metastasis in the short term. In the era of chemotherapy, studies have indicated the potential survival benefits of consolidative thoracic radiotherapy (cTRT) for patients responding to systemic treatment. The introduction of immunotherapy has significantly transformed the treatment landscape for SCLC. The combination of immune checkpoint inhibitors (ICIs) with chemotherapy has emerged as the new standard for first-line treatment of ES-SCLC. Nevertheless, controversy surrounds the role of cTRT after the first-line treatment of ES-SCLC in the context of immunotherapy, especially considering advancements in imaging staging methods and precise radiotherapy technology. This review focuses on the application value and latest research advancements in cTRT following first-line immunotherapy combined with chemotherapy in ES-SCLC, providing valuable insights for clinical practice.